The Effect of Essential Oils of Citronella and Patchouli Oil on Growth of Botryodiplodia sp. In Vitro - Muhammad Alam Firmansyah; Anuraga Jayanegara; Mafrika Ria Gita Solaya; Ikhwan Shodiq Syifaudin (Jurnal Silvikultur Tropika, 2023)
Pathogen Botryodiplodia sp. is a fungus that causes dieback and stems rot diseases that attack forestry plants. The control currently being used in the field is using chemical pesticides, which are harmful to the surrounding environment and the plant itself, so there is a need for another alternative, namely using citronella and patchouli essential oils. Essential oils of citronella and patchouli have active compounds that act as antifungals to inhibit the growth of the pathogenic fungus Botryodiplodia sp. This study aimed to analyze the effect of citronella and patchouli essential oils on inhibiting the growth of the pathogen Botryodiplodia sp. in vitro. The results showed that the 10% patchouli treatment had the highest PDA and PDB media inhibition value. The lowest inhibition value was found in the 1% citronella treatment. The level of concentration, type of oil, and active ingredients contained in the oil affect the increase in effectiveness in controlling the pathogen Botryodiplodia sp. Keywords: antifungal, Botryodiplodia sp., citronella, in vitro, patchouli